Errancies of desire : monstrous masculinities across the Atlantic - Messier, Vartan P. (Television series (Syracuse, N.Y.), 2023)
"Errancies of Desire details the ways in which male desire is predicated on mediated forms of predatory and misogynistic sexuality that cross national and cultural divides. The book effectively argues that when associated symptoms of violent and sexist behavior are institutionalized and misguidedly construed as a masculine norm, all men become monsters"--